The Link Between Economic Growth and Tourism: Covid-19 Impact - Oleksii LYULYOV; Yana US; Tetyana PIMONENKO; Aleksy KWILINSKI; Tetyana VASYLIEVA; Nataliya DALEVSKA; Jan POLCYN; Viktoriia BOIKO (Communications of International Proceedings, 2020)
This paper deals with the investigation of the relationship between tourism and economic growth. The research theoretically proved modern tourism was a wide-spread dynamic industry with high impact on economic development, damaged by COVID-19 crisis. This paper aims to analyse changes in the tourism industry to forecast recovering of tourism activity in the view of quarantine restrictions. For achieving the goals, the authors used the extrapolation model ARIMA. The object is the routs plotting requests of Apple users in Poland, Estonia, Latvia, Lithuania, Hungary and Czechia from 13 January to 9 May 2020. The forecast has been conducted under several conditions as follows: 1) without the introduction of quarantine restrictions from 11.03.2020; 2) taking into account the quarantine restrictions on movements. The findings demonstrated that the adopted quarantine measures have a significant impact on overcoming the recession in the tourism industry in conditions of economic, social and political tension. Herewith, there is a slight positive tendency in recovering tourism. The results provide background for future researchers on developing a strategy to overcome the tourism recession.
Keywords: COVID-19; Domestic Tourism; Economic Growth; Pandemic; Tourism